PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DALAM PEMBELAJARAN MATERI BANGUN RUANG SISI DATAR DI KELAS VIII SMPN SATAP JIKO BELANGA - James U.L Mangobi; Ontang Manurung; Suliasti Nevaria Martelu (LPPM Universitas Bina Bangsa, 2023)
This research aims to compare the learning outcomes of students who are taught using the PBL model with the KBM value set by the school of 75. This type of research is experimental with a one-shot case study design, namely providing treatment to one experimental group or class. Finally, an evaluation will be given in the form of a final test. This research was conducted at SMPN Satap Jiko Belanga, Nuangan District, East Bolaang Mongondow Regency in the even semester of the 2023–2024 academic year by taking class VIII as an experimental class consisting of 20 students. The variables in this research are student learning outcomes in the material, Building Flat Side Spaces. Data was collected by giving a final test (post-test) to students after learning was carried out using the PBL model. The data analysis used to test the hypothesis is one-group t-test statistics. The results of the research show that the learning outcomes of Building Flat Side Spaces for students taught using the PBL model exceed the KBM value set by the school of 75